In situ-formed nitrogen-doped carbon/silicon-based materials as negative electrodes for lithium-ion batteries - Monje, Ivonne E.; Sanchez-Ramirez, Nedher; Santagneli, Silvia H. [UNESP]; Camargo, Pedro H.; Bélanger, Daniel; Schougaard, Steen B.; Torresi, Roberto M. (Elsevier, 2021)
The development of negative electrode materials with better performance than those currently used in Li-ion technology has been a major focus of recent battery research. Here, we report the synthesis and electrochemical evaluation of in situ-formed nitrogen-doped carbon/SiOC. The materials were synthesized by a sol–gel process using 3-(aminopropyl)triethoxysilane (APTES), sodium citrate and glycerol. The electrochemical performance of pyrolyzed materials was studied using poly(acrylic acid) binder and commercial organic electrolyte. Our reported approach enables changes in both the amount of nitrogen and the morphology as a function of the molar ratio of APTES:citrate and reaction time. Spherical-shaped NC/SiOC composite electrodes deliver a delithiation capacity of 622 mAh/g at 0.1 A/g and an initial coulombic efficiency of ∼63%, while in the large bulk material, respective values of 367 mAh/g and ∼55% were obtained. After 1000 charge/discharge cycles at 1.6 A/g, the latter material exhibits 98% of the initial capacity once it returned to lower current cycling. Overall, our results indicate that NC/SiOC materials are quite promising for electrochemical applications since both their large capacity and stability demonstrate superior performance compared to traditional graphite. Moreover, our synthesis is simple and, more importantly, environmentally friendly chemicals, such as sodium citrate and glycerol, are used.
Keywords: Lithium-ion batteries; Negative electrode; Nitrogen-doped carbon; Silicon oxide; Silicon oxycarbide